Feed Composition Analysis and Reproductive Status of Dairy Cows Raised in Yogyakart - Firdaus Hudaya, Mohammad; Tri Widayati, Diah; Prasetyo Widyobroto, Budi; Tri Noviandi, Cuk (International Journal of Engineering and Technology, 2018)
The objective of this study was to determine the content of the feed given and reproductive status of each animal and its effect on reproduction performance in early lactation dairy cows. Seven early lactation of Friesian Holstein cows were used from local farmer. The observed variable were feedstuff from local farmer and reproductive status (post partum estrous and service per conception). The results of proximat and van soest analysis from feedstuff consist of elephant grass (Pennisetum purpureum) and concentrate feed from feed mill. The elephant grass (Pennisetum purpureum) was contained of dry matter (DM) 86.27%, Ash 18.63%, extract eter (EE) 3.84%, crude fiber (CF) 30.62%, crude protein (CP) 13.05%, neutral detergent fibre (NDF) 73.73% and acid detergent fiber (ADF) 45.31%. Concentrates feed was contained of dry matter (DM) 89.24%, Ash 15.36%, extract eter (EE) 5.37%, crude fiber (CF) 17.11%, crude protein (CP) 12.76%, neutral detergent fibre (NDF) 58.23% and acid detergent fiber (ADF) 19.20%. The results of reproductive parameters for post partum estrous (PPE) 121.43Â±16.672 days and service per conception (S/C) was 2.14Â±0.690. In conclusion the feedstuff were given less meet the requirement, and affecting the performance of reproduction.Â Â